2006
DOI: 10.1016/j.ssc.2006.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroic TbMnO3 nanoparticles

Abstract: We report on the synthesis of TbMnO 3 nanoparticles by chemical co-precipitation route and their structural, chemical bonding, magnetic and dielectric properties. It is shown that the interesting multiferroic properties of this system as reflected by the concurrent occurrence of magnetic and dielectric transitions are retained in the nanoparticles (size ~40 nm). However, the nanoparticle constitution and properties are seen to depend significantly on the calcination temperature. While the nanoparticles obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Because RMnO 3 materials have the same crystal structure and their magnetic phase diagrams can be controlled by modulating the effective R ion radius by partial substitution of lanthanoids, RMnO 3 nanoparticles are an excellent testbed to study the effect of R ion size on magnetic properties. Previous studies have reported that nanoparticles of DyMnO 3 with a particle size of 8.6–106 nm, , GdMnO 3 with a particle size of 52–270 nm, and TbMnO 3 with a particle size of 25 nm to 3 μm exhibited different behaviors from bulk crystals owing to changes in the particle size. In the case of RMnO 3 bulk crystals, the magnetic properties and crystal structure have been investigated as a function of lanthanoid ionic radius; however, to the best of our knowledge, there have been no reports comparing the size dependence of magnetic properties and the crystal structure of RMnO 3 nanoparticles with similar particle size (approximately 10 nm) and different R ions.…”
Section: Introductionmentioning
confidence: 98%
“…Because RMnO 3 materials have the same crystal structure and their magnetic phase diagrams can be controlled by modulating the effective R ion radius by partial substitution of lanthanoids, RMnO 3 nanoparticles are an excellent testbed to study the effect of R ion size on magnetic properties. Previous studies have reported that nanoparticles of DyMnO 3 with a particle size of 8.6–106 nm, , GdMnO 3 with a particle size of 52–270 nm, and TbMnO 3 with a particle size of 25 nm to 3 μm exhibited different behaviors from bulk crystals owing to changes in the particle size. In the case of RMnO 3 bulk crystals, the magnetic properties and crystal structure have been investigated as a function of lanthanoid ionic radius; however, to the best of our knowledge, there have been no reports comparing the size dependence of magnetic properties and the crystal structure of RMnO 3 nanoparticles with similar particle size (approximately 10 nm) and different R ions.…”
Section: Introductionmentioning
confidence: 98%
“…Magnetoelectric coupling can be found in a variety of materials including bulk structures, thin-film heterostructures, and nanoparticles [10][11][12][13][14]. The various mechanisms and symmetries involved in magnetoelectric materials are often competing and producing magnetic and lattice frustration [6].…”
mentioning
confidence: 99%
“…Smaller-size RE 3+ (Ho to Lu, and Y) adopt a hexagonal structure and present both ferroelectric and antiferromagnetic orderings, and for this reason, are known as ''multiferroic materials''. It has been shown that microstructure is a key parameter to control both properties, for instance, in nanosized particles of TbMnO 3 [1] or artificially-engineered nanostructures [2]. Substitution of Y in orthorhombic manganites promotes a multiferroic state with spontaneous electric polarization and modulated antiferromagnetism [3].…”
mentioning
confidence: 99%